Championing Inclusivity: Underrepresentation of Women in African Academic Leadership and Scholarly Journal Management - Mwaura, Job; Balliah, Dinesh (Evidence Based Library and Information Practice, 2024)
Objectives – This study seeks to investigate the exclusion of women from the management of scholarly journals across East Swahili (Kenya, Uganda, Tanzania, South Sudan, Ethiopia, and Anglo-West Africa (Ghana, Nigeria, Sierra Leone, Liberia, Gambia) by delving into the implications of marginalization. Furthermore, the study aims to illuminate the often-overlooked experiences of black women, whose narratives are frequently overshadowed by those of black men or subsumed within the context of white women.Methods – By employing empirical evidence from African Journals Online (AJO) and institutional journal data from countries in focus, this study examines the pervasive domination of men within scholarly journal management in East Swahili and Anglo-West Africa.Results – Findings reveal a widespread dominance of men in the management of scholarly journals in the targeted countries despite the considerable presence of women in academia.Conclusion – The underrepresentation of women in academic leadership positions carries significant consequences, including a lack of diversity in decision-making processes. Such homogeneity can perpetuate existing disparities and impede progress towards gender equality within academia. Furthermore, discussions concerning gender inequality in academia often neglect the experiences of black women.